Cypriot and Greek nurses' perceptions of the professional practice environment - Papastavrou, Evridiki; Efstathiou, Georgios; Lemonidou, Chryssoula; Kalafati, Maria; Katajisto, Jouko; Suhonen, Riitta (My University, 2014)
Research evidence supports that the role of the professional practice environment is crucial for the delivery of quality care as it is significantly correlated with patient and nurse outcomes. However, in countries sharing similar cultural and ethnic backgrounds, like Cyprus and Greece, as well as the increased mobility of patients and healthcare workers, there is a lack of information regarding this issue. The aim of this study is to explore and compare Cypriot and Greek nurses' perceptions of their professional practice environment. Methods A descriptive comparative survey was employed using a sample of nurses in Cyprus (N = 150) and Greece (N = 147). Information was collected with the Revised Professional Practice Environment Scale (RPPE). Results The results revealed significant differences between the two countries in three out of eight factors of the RPPE, with Greece's mean value being higher than Cyprus's: Handling Disagreements and Conflicts, Leadership and Autonomy in Clinical Practice, and Teamwork. Conclusions The findings generate additional knowledge about the organizational context of care delivery that might help nursing leaders to understand how nurses perceive their work environment and how this influences their work, and consequently the care provided. The results can be utilized by nurse ward managers to improve the quality of nursing care provided. Further research is needed using different approaches to explore nurses' experience in more depth. Implications for nursing or health policy Measuring nurses' perceptions of their professional practice environment may assist managers and policymakers in introducing interventions that contribute to a better practice environment and consequently to improved nursing, as well as patient, outcomes.
Keywords: Care; Cyprus; Greece; Nurse; Professional practice environment